The Handbook of Global Media Research - Volkmer, Ingrid (Handbooks in Communication and Media, 2012)
"Bringing together the perspectives of more than 40 internationally acclaimed authors, The Handbook of Global Media Research explores competing methodologies in the dynamic field of transnational media and communications, providing valuable insight into research practice in a globalized media landscape. Provides a framework for the critical debate of comparative media research Posits transnational media research as reflective of advanced globalization processes, and explores the role and responsibility this bestows it with Articulates the key themes and competing methodological approaches in a dynamic and developing field Showcases the perspectives and ideas of 30 leading internationally acclaimed scholars Offers a platform for the discussion of crucial issues from a variety of theoretical, methodical and practical viewpoints"--